The FORCE Fitness Profile—Adding a Measure of Health-Related Fitness to the Canadian Armed Forces Operational Fitness Evaluation. (November 2015) - Gagnon, Patrick; Spivock, Michael; Reilly, Tara; Mattie, Paige; Stockbrugger, Barry
Abstract : Abstract: Gagnon, P, Spivock, M, Reilly, T, Mattie, P, and Stockbrugger, B. The FORCE fitness profile—adding a measure of health-related fitness to the Canadian Armed Forces operational fitness evaluation. J Strength Cond Res 29(11S): S192–S198, 2015—In 2013, the Canadian Armed Forces (CAF) implemented the Fitness for Operational Requirements of Canadian Armed Forces Employment (FORCE), a field expedient fitness test designed to predict the physical requirements of completing common military tasks. Given that attaining this minimal physical fitness standard may not represent a challenge to some personnel, a fitness incentive program was requested by the chain of command to recognize and reward fitness over and above the minimal standard. At the same time, it was determined that the CAF would benefit from a measure of general health-related fitness, in addition to this measure of operational fitness. The resulting incentive program structure is based on gender and 8 age categories. The results on the 4 elements of the FORCE evaluation were converted to a point scale from which normative scores were derived, where the median score corresponds to the bronze level, and silver, gold, and platinum correspond to a score which is 1, 2, and 3 SDs above this median, respectively. A suite of rewards including merit board point toward promotions and recognition on the uniform and material rewards was developed. A separate group rewards program was also tabled, to recognize achievements in fitness at the unit level. For general fitness, oxygen capacity was derived from FORCE evaluation results and combined with a measure of abdominal circumference. Fitness categories were determined based on relative risks of mortality and morbidity for each age and gender group. Pilot testing of this entire program was performed with 624 participants to assess participants' reactions to the enhanced test, and also to verify logistical aspects of the electronic data capture, calculation, and transfer system. The newly dubbed fitness profile program was subsequently approved by the senior leadership of the CAF and is scheduled to begin a phased implementation in June 2015.